Debt-equity bias should be addressed on national rather than on EU level - Christoph Spengel; Leonie Fischer; Christopher Ludwig; Jessica Müller; Stefan Weck; Sarah Winter (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
The economic crisis following the COVID-19 pandemic has increased the debt levels of corporations and reduced the level of investments. From a tax perspective, interest payments on debt are generally deductible from the corporate tax base, while costs related to equity are not. This debt-equity bias is a deep-rooted issue in today's tax system and inhibits equity-financed investments. From a microeconomic perspective, the bias leads to socially undesirable inefficiencies in capital markets, resulting in welfare losses. From a macroeconomic point of view, high debt levels hinder economic growth. To provide a stable and supportive tax environment for a sustainable recovery after the corona crisis, the European Commission has published a framework on "Business Taxation for the 21st Century" in May 2021. Besides other (long-term) proposals, a debt equity bias reduction allowance (DEBRA) should be developed to address the tax-induced distortions of debt financing. For a legislative proposal, the European Commission identified three possible concepts: First, a Comprehensive Business Income Tax (CBIT) that disallows the tax-deductibility of any financing cost. Second, an Allowance for Corporate Equity (ACE) that provides for the deductibility of notional interest on either all equity or new equity. And third, an alignment of the treatment of debt and equity financing by deducting a notional return on all capital, namely an Allowance for Corporate Capital (ACC).
Keywords: 330